MODERN METHODS OF DIAGNOSTICS OF THYROID DISEASES IN CHILDREN (International Conference on Scientific Research in Natural and Social Sciences, 2025)
Thyroid diseases in children are becoming increasingly recognized as a significant health concern, with diagnoses of conditions such as hypothyroidism, hyperthyroidism, and thyroid cancer on the rise. Early diagnosis is essential to mitigate the impact of these diseases on growth, development, and overall well-being. This article aims to provide an overview of modern diagnostic methods for thyroid diseases in pediatric populations. These include clinical evaluation, biochemical tests, imaging techniques, and molecular diagnostic tools, all of which contribute to a more accurate and timely diagnosis. This review also highlights advancements in genetic screening, ultrasonography, and other innovative approaches to enhancing diagnostic accuracy.